Building a Culture of Safety among Future Maritime Leaders in Indonesia - Hesti Ekawati (The International Science of Health Journal, 2024)
This research investigates the implementation and perception of Occupational Safety and Health (K3) among cadets in the Port and Shipping Management program at the Jakarta Maritime Institute. Through qualitative interviews and surveys with 50 cadets, key K3 aspects such as hazard identification, safe work practices, and physical health were examined. The results reveal a strong emphasis on preventing accidents and injuries, while also highlighting areas for improvement in mental health, healthy lifestyles, and productivity-related aspects. Additionally, the research assesses the alignment of K3 practices with international standards and regulations, such as the Standards of Training, Certification, and Watchkeeping for Seafarers (STCW) established by the International Maritime Organization (IMO). While certain K3 aspects and regulations are compliant, there are opportunities for further improvement to ensure full alignment. The implications of the research extend to policy and practice in the maritime industry, emphasising the importance of continuous evaluation and refinement of K3 practices to foster a stronger safety culture among future maritime leaders and enhance the overall safety and health of workers in the maritime sector.